Top Indian Incomes, 1922-2000 - Banerjee, Abhijit; Piketty, Thomas (Published by Oxford University Press on behalf of the World Bank, 2014)
This article presents data on the evolution of top incomes and wages for 1922-2000 in India using individual tax return data. The data show that the shares of the top 0.01 percent, 0.1 percent, and 1 percent in total income shrank substantially from the 1950s to the early to mid-1980s but then rose again, so that today these shares are only slightly below what they were in the 1920s and 1930s. This U-shaped pattern is broadly consistent with the evolution of economic policy in India: from the 1950s to the early to mid-1980s was a period of ''socialist'' policies in India, whereas the subsequent period, starting with the rise of Rajiv Gandhi, saw a gradual shift toward more pro-business policies. Although the initial share of the top income group was small, the fact that the rich were getting richer had a nontrivial impact on the overall income distribution. Although the impact is not large enough to fully explain the gap observed during the 1990s between average consumption growths shown in National Sample Survey based data and the national accounts based data, it is sufficiently large to explain a non-negligible part of it.